Kualitas Pelayanan Publik (Studi Kasus Pengesahan Pajak Tahunan Kendaraan Roda Dua Pada Kantor Samsat Pekanbaru Selatan) - HANDAYANI, MUSTIKA FEBRI; YULIANI, FEBRI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Office SAMSAT which stands for "System Administration Manunggal under one roof" where the office is under the auspices of the Government of Riau Province, It said the roof because the office is linked by three agencies:1. Pekanbaru City Police2. Riau Provincial Revenue Office3. Prog Pekanbaru city branchWhere the above three agencies together in one system and collaboration processes executed on the building, that provide convenience and improve service to taxpayers. The tax itself is a mandatory contribution to the region owed by private persons or entities that are forced by the law to not get rewarded directly and used for the purposes of the area for the greatest welfare of the people (Act No. 28 of 2009 on local taxes and levies), of understanding shows that people are obliged to contribute to the region, and should the public get quality service. But the fact that the service still have problems, such as local people do not understand that no changes to the existing regulations in Kesamsatan, ecause these changes at any time to change. And the changes are not socialized to people. The purpose of this study was to determine how the quality of public services in terms of annual tax ratification of two-wheeled vehicles in South Pekanbaru SAMSAT office.Concepts that researchers use the theory by Agus Dwiyanto there are several dimensions of services quality are : attitude officers, procedures, time, facilities, service. This research uses descriptive method with qualitative approach. Data obtained though interviews submitted to the informant and then analyzed by researchers. It also collected secondary data relating to the issues under investigation.has not run optimally. There is a weakness-weakness concerning the quality of services such as : The lack of socialization to the community officers about the latest regulations to which they apply and the not fit punctuality in accordance with the existing standart operating procedures, still the tendency of officers to provide services that are not fair to the tax payers.Keywords : The quality, Public Service, Samsat Pekanbaru Selatan.